8-2(n+3)=n+7-3n
We move all terms to the left:
8-2(n+3)-(n+7-3n)=0
We add all the numbers together, and all the variables
-2(n+3)-(-2n+7)+8=0
We multiply parentheses
-2n-(-2n+7)-6+8=0
We get rid of parentheses
-2n+2n-7-6+8=0
We add all the numbers together, and all the variables
-5!=0
There is no solution for this equation
Answer:
The measure of arc SQ is 95° ⇒ (1)
Step-by-step explanation:
- The measure of any circle is 360°
- The measure of the subtended arc to an inscribed angle is twice the measure of this angle
In the given circle
∵ S lies on the circumference of the circle
∴ ∠QSR is an inscribed angle
∵ ∠QSR is subtended by arc QR
→ By using the 2nd rule above
∴ m arc QR = 2 × m∠QSR
∵ m∠QSR = 95°
∴ m arc QR = 2 × 95
∴ m arc QR = 190°
→ By using the 1st rule above
∵ m of the circle = m arc QR + m arc SQ + m arc SR
∵ m arc SR = 75° and m arc QR = 190°
→ Substitute them in the equation above
∴ 360 = 190 + m arc SQ + 75
→ Add the like term in the right side
∴ 360 = 265 + m arc QS
→ Subtract 265 from both sides
∵ 360 - 265 = 265 - 265 + m arc SQ
∴ 95° = m arc SQ
∴ The measure of arc SQ is 95°
Answer:
1. x=8 2. x=
Step-by-step explanation:
1. 17^2-15^2= 64
=8
x=8
sorry i only know 1
Answer:
f(x)= 10,000(2)^x
Step-by-step explanation:
Exponential equations can be modeled by a(r)^x where a is the initial amount, r is the difference, and x is how many units the equation should be squared by.